KOMUNIKASI INTERPERSONAL ORANG TUA DENGAN ANAK DALAM MENCEGAH LGBT PERSPEKTIF AL-QURAN - Muhammad Solihin; Akhmad Rifa’i; Robby Aditya Putra (Nizham Jurnal Studi Keislaman, 2023)
Abstract In Indonesia, the number of cases involving LGBT (Lesbian, Gay, Bisexual, And Transgender) individuals continues to rise. It is anticipated that parental role will prevent children from engaging in sexual behavior. From the perspective of the Qur'an, this article presents descriptive analytic methods for illustrating how interpersonal communication between parents and children can help prevent LGBT. According to the review, interpersonal communication between parents and children is crucial to preventing LGBT behavior. Preventing LGBT behavior through interpersonal communication between parents and children. Before explaining the dangers of LGBT behavior, the Koran's perspective can be started with openness, empathy, support, equality, and a positive attitude. It is hoped that parents will be better able to encourage their children to express what is on their minds so that they can communicate effectively through honesty and openness. Keywords: Interpersonal Communication, LGBT, Al-Qur'an Perspective Abstrak Di Indonesia, jumlah kasus yang melibatkan individu LGBT (lesbian, gay, biseksual, dan transgender) terus meningkat. Peran orang tua diharapkan akan mencegah anak-anak untuk melakukan perilaku seksual. Dari perspektif Al-Qur'an, artikel ini menyajikan metode analisis deskriptif untuk menggambarkan bagaimana komunikasi interpersonal antara orang tua dan anak dapat membantu mencegah LGBT. Menurut review, komunikasi interpersonal antara orang tua dan anak sangat penting untuk mencegah perilaku LGBT. Mencegah perilaku LGBT melalui komunikasi interpersonal antara orang tua dan anak. Sebelum menjelaskan bahaya perilaku LGBT, perspektif Alquran bisa dimulai dengan keterbukaan, empati, dukungan, kesetaraan, dan sikap positif. Diharapkan para orang tua lebih mampu mendorong anaknya untuk mengungkapkan apa yang ada di pikirannya sehingga dapat berkomunikasi secara efektif melalui kejujuran dan keterbukaan. Kata Kunci: Komunikasi Interpersonal, LGBT, Perspektif Al-Qur'an